THE ROLE OF CADRES TO VISIT THEIR ELDERLY IN THE COVID-19 PANDEMIC - Karyo (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Elderely Posyandu is service post for societies an advanced age in a certain region any obstacles elderly in following Posyandu is mostly elderly did not know the schedule of posyandu. Hence research is to analyze the relation between role of Posyandu cadre and the elderly to visit elderly Posyandu. The design of this study was descriptive research consists of two variables namely the role of cadres an visit posyandu elderly. The population enrolled in the elderly posyandu was 56 people and the sample size 37 respondents.Sampling techbique using purposive samples of data collection techniques namely primary data for the role of posyandu cadres and secondary data of elderly visits taken from posyandu regrister. The research result of the respondens, 37 cadres role is not 62,1% and elderly who are not routine visit to posyandu 64,8%. Senior cadres who said posyandu play a role and elderly who regularly 10 visit people (71,4%), Whereas in the cadre who did not play role of posyandu not routine 21 people (91,3%). The role of cadres is one of the things that affect the elderly to visit Posyandu. It is recommended that solid foundation oc cadres of posyandu further increase its role. So the elderly routinely visit the Posyandu.